1995
DOI: 10.1016/0735-1097(95)00358-4
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of muscular ventricular septal defect in neonates

Abstract: There is a prevalence of muscular ventricular septal defect in neonates of 53.2/1,000 live births. The patients were asymptomatic, and 88.9% had defects that closed spontaneously within 1 to 10 months. These defects may be caused by environmental factors. In many cases, muscular ventricular septal defect may also result from delayed physiologic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
121
2
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(137 citation statements)
references
References 18 publications
12
121
2
2
Order By: Relevance
“…8,22 Muscular ventricular defects, in particular, tend to be clinically mild or even asymptomatic and have been detected in as many as 5% of newborns screened by color-Doppler echocardiography. 24 The increased rate of atrioventricular septal defect among infants with Down syndrome in our study is consistent with previous reports 25 and also may reflect a more intensive or earlier cardiologic evaluation of affected pregnancies, newborns, or young infants. The racial variations in this study offer additional, if indirect, clues to understanding such time trends.…”
Section: Discussionsupporting
confidence: 82%
“…8,22 Muscular ventricular defects, in particular, tend to be clinically mild or even asymptomatic and have been detected in as many as 5% of newborns screened by color-Doppler echocardiography. 24 The increased rate of atrioventricular septal defect among infants with Down syndrome in our study is consistent with previous reports 25 and also may reflect a more intensive or earlier cardiologic evaluation of affected pregnancies, newborns, or young infants. The racial variations in this study offer additional, if indirect, clues to understanding such time trends.…”
Section: Discussionsupporting
confidence: 82%
“…small VSDs, 36 or have no functional effects on the heart. On the basis of the published literature, we assumed that the prevalence of ventricular septal defect would increase by 95% with echocardiography in the newborn period 36,273 and the prevalence of PDA, ASD, and PS by 61%.…”
Section: Sources Of Datamentioning
confidence: 99%
“…small VSDs, 36 or have no functional effects on the heart. On the basis of the published literature, we assumed that the prevalence of ventricular septal defect would increase by 95% with echocardiography in the newborn period 36,273 and the prevalence of PDA, ASD, and PS by 61%. The 11 The number of defects that would be detecting using echocardiography in 100,000 liveborn infants is calculated and displayed in the three right-hand columns of the prevalence table in Appendix 8.…”
Section: Sources Of Datamentioning
confidence: 99%
“…Studies done on newborn infants, including some with no murmurs, found incidence of this heart defect to be from 2% to 5%. 8,9 About 85% to 90% of these defects close spontaneously by one year of age. 8,[10][11][12][13] In the initial stages, the shunt through the defect is from left ventricle to right.…”
Section: Discussionmentioning
confidence: 99%